Analisis Metode Happy When Sick (HWS) dalam Bimbingan Rohani di Rumah Sakit - Pujiono, Pujiono; Haryanto, Budi (Program Studi Bimbingan dan Konseling Islam, 2024)
Along with the times and the complexity of the problems faced by humans, especially those who are facing illness, the problems of patients in hospitals are not only physical but also psychological, such as anxiety. Therefore, spiritual guidance is considered important to support the healing process by helping patients accept their condition with sincerity, patience and trust. An effective method is needed so that the aims and objectives of achieving healing, both physical and spiritual, can be achieved. This study aims to analyze the effectiveness of the HWS (Happy When Sick) method in Islamic spiritual guidance at Muhammadiyah Hospital using qualitative descriptive methods. Data was collected through observation and in-depth interviews, then analyzed using the interactive model of Miles, Huberman, and Saldana. The results show that the application of the HWS method has a positive impact on the psychological and spiritual condition of patients from various generations, families and medical personnel. Patients show increased calm, enthusiasm for worship, and optimism regarding recovery, as well as reduced anxiety and increased compliance with medical recommendations. This research recommends the integration of holistic and adaptive spiritual guidance methods to optimally support patients' physical and spiritual health.